High-Speed Automotive Networking and Signal Integrity: A Comprehensive Analysis Of 10G Ethernet Implementation, Electromagnetic Interference Mitigation, And Post-Quantum Security in Autonomous Driving Systems (Emerging Indexing of Global Multidisciplinary Journal, 2026)
The rapid evolution of Autonomous Driving Assistance Systems (ADAS) and the transition toward fully autonomous vehicular architectures have necessitated a paradigm shift in intra-vehicle communication bandwidth. As sensory suites-comprising high-resolution LIDAR, 4K camera arrays, and ultrasonic sensors-generate unprecedented data volumes, traditional Controller Area Network (CAN) protocols have proven insufficient. This research investigates the deployment of 10 Gb/s Automotive Ethernet as the backbone for next-generation vehicular networks. The study specifically focuses on the dual challenges of physical layer reliability and cryptographic resilience. First, we examine the mitigation of Electromagnetic Interference (EMI) in high-speed camera Printed Circuit Board (PCB) designs within lighting control modules, utilizing validation techniques to ensure signal integrity in harsh automotive environments. Second, the paper addresses the emerging threat landscape posed by quantum computing to vehicular security. By evaluating Post-Quantum Cryptography (PQC) candidates, specifically the FALCON digital signature scheme, we propose a framework for securing 10G interfaces against future decoupled adversarial attacks. The methodology transitions from a theoretical exploration of signal attenuation and shielding effectiveness to a practical evaluation of virtual machine migration and burst-mode transmission within time-sensitive networking. Our results indicate that while 10G Ethernet provides the requisite throughput for real-time sensor fusion, its implementation requires rigorous adherence to differential pair routing and advanced shielding to prevent EMI-induced data loss. Furthermore, the integration of PQC ensures long-term data authenticity without compromising the low-latency requirements of safety-critical ADAS functions. This article provides a holistic roadmap for the integration of high-bandwidth, EMI-resilient, and quantum-secure communication infrastructures in the automotive sector.